Swimming at different temperatures: The lipid composition of sperm from three freshwater fish species determined by mass spectrometry and nuclear magnetic resonance spectroscopy - Engel, Kathrin M; Sampels, Sabine; Dzyuba, Borys; Podhorec, Peter; Policar, Tomáš; Dannenberger, Dirk; Schiller, Jürgen (Chemistry and physics of lipids, 2019)
The spawning behavior of different fish species is as diverse as their habitats. A lot of factors influence the (phospho)lipid composition of fish sperm, including the water temperature at which spawning takes place. Therefore, this study aimed on the elucidation of the phospholipid composition of sperm from three fish species from different orders (common carp - Cyprinus carpio, northern pike - Esox lucius and burbot - Lota lota) with different spawning temperatures by nuclear magnetic resonance spectroscopy (NMR), matrix-assisted laser desorption/ionization mass spectrometry and thin-layer chromatography (TLC) coupled to electrospray ionization mass spectrometry as well as gas chromatography. Next to the lipid composition that was different for carp, northern pike and burbot, regarding the moieties of the different (phospho)lipid classes (particularly sphingomyelin and acidic phospholipids) and the saturation degree of the fatty acyl residues, there were differences observed depending on the analytical method that was used. The results from TLC and NMR investigations differed regarding the amounts of the different phospholipids. Reasons for these discrepancies are discussed in detail.
Keywords: Temperature; druhová specificita; Male; Spermatozoa; magnetická rezonanční spektroskopie; Magnetic Resonance Spectroscopy; mužské pohlaví; sladká voda; NMR; Fresh Water; Species Specificity; Fish sperm; ryby; Fishes; lipidy; plavání; Animals; Swimming; zvířata; Mass spectrometry; spermie; spektrometrie hmotnostní - ionizace laserem za účasti matrice; Lipid composition; Lipids; teplota; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; TLC